2022
DOI: 10.3390/biomedicines10092063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Monoclonal Antibodies in the Treatment of High-Risk Patients with SARS-CoV-2 Breakthrough Infections: The ORCHESTRA Prospective Cohort Study

Abstract: The clinical impact of anti-spike monoclonal antibodies (mAb) in Coronavirus Disease 2019 (COVID-19) breakthrough infections is unclear. We present the results of an observational prospective cohort study assessing and comparing COVID-19 progression in high-risk outpatients receiving mAb according to primary or breakthrough infection. Clinical, serological and virological predictors associated with 28-day COVID-19-related hospitalization were identified using multivariate logistic regression and summarized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The H2020-funded ORCHESTRA project (Connecting European Cohorts to Increase Common and Effective Response to SARS-CoV-2 Pandemic) includes work package 2 (WP2), prospectively enrolling high-risk patients receiving early treatment for symptomatic COVID-19. Clinical efficacies of bamlanivimab, bamlanivimab/etesevimab, casirivimab/imdevimab, or sotrovimab in 740 mild-to-moderate non-hospitalized COVID-19 patients have been described (19, 20) (for eligibility criteria, see Supplementary Table 1 ). From the WP2 cohort, patients were prospectively invited to a sub-study assessing immunological and virological responses to mAbs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The H2020-funded ORCHESTRA project (Connecting European Cohorts to Increase Common and Effective Response to SARS-CoV-2 Pandemic) includes work package 2 (WP2), prospectively enrolling high-risk patients receiving early treatment for symptomatic COVID-19. Clinical efficacies of bamlanivimab, bamlanivimab/etesevimab, casirivimab/imdevimab, or sotrovimab in 740 mild-to-moderate non-hospitalized COVID-19 patients have been described (19, 20) (for eligibility criteria, see Supplementary Table 1 ). From the WP2 cohort, patients were prospectively invited to a sub-study assessing immunological and virological responses to mAbs.…”
Section: Resultsmentioning
confidence: 99%
“…As several studies have shown that immunocompromised individuals show a prolonged carriage of SARS-CoV-2 (5, 7), we investigated whether these patients receiving mAb therapy also carried higher viral loads. Immunocompromised status was defined clinically on the basis of patients on active immunosuppressive treatment for cancer or immunological diseases, as described (19, 20). We showed that immunocompromised patients had higher viral loads at the time of enrolment within the mAb treatment groups (ΔCt 3.03 and 2.76 for ORF1ab and N , respectively; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations